Bevacizumab Eligibility in Patients with Metastatic and Recurrent Cervical Cancer: A Retrospective Review. (1st June 2018) - Skelton, William Paul; Castagno, Jacqueline; Cardenas-Goicoechea, Joel; Daily, Karen; Yeung, Anamaria; Markham, Merry Jennifer
Objective: Bevacizumab is approved for use in combination with chemotherapy for metastatic/recurrent cervical cancer (CC), with increased survival/response rates. However, use of bevacizumab is not always feasible or safe. The purpose of this study was to identify the percentage of metastatic/recurrent CC patients at our institution who would have been eligible to receive bevacizumab. Methods: A retrospective study was conducted to identify metastatic/recurrent CC patients treated at UFHealth between 2006 and 2016. Chart review was performed to determine if the patient met bevacizumab eligibility criteria. Results: In total, 79 patients with metastatic/recurrent CC were identified; 85.5% would have been ineligible to receive bevacizumab, and 14.5% would have been eligible. The most common reason for exclusion was active bleeding (68.4%); 94% of which was vaginal. In all, 27.6% would be excluded due to poor renal function, and 23.7% due to poor performance status (PS). Conclusions: Despite improved survival, only 14.5% of metastatic/recurrent CC patients treated over a 10-year period would have been eligible to receive bevacizumab. Most patients would have been excluded due to active bleeding, most commonly vaginal bleeding, a common complication from their disease. Identifying novel therapies for metastatic/recurrent CC patients with improved safety profiles that would allow for their use in this challenging population is critical.